QUALITY PERFORMANCE MANAGEMENT DEVELOPMENT TEACHER : Study Planning, Implementation, and Monitoring Development Primary School Teachers' Performance in Tegal, Central Java - Rozano, Dino (2010)
This study aims to determine the factual conditions of the management of development of primary school teachers' performance in Tegal focused some research questions: what are the planning, implementation, monitoring and evaluation, as well as the impact of development of quality of primary school teachers in Kota Tegal? The reflective question is "what is the conceptual model of quality development management performance of primary school teachers that may be implemented within the framework of improving the quality of education at primary schools in Tegal? Theoretically, the research question is explained by the concepts of human resource development; development of quality teachers in the regional autonomy policy, and managerial procedures of development of teachers' quality. This research uses a qualitative approach, interviews, observation, and study documentation as techniques of data collection. Research findings are summarized below. First, the quality development plan primary school teachers in Tegal, is inseparable from the strategic plan (Strategic Plan) development of education as the reference. Second, the important aspects of the implementation of quality development of primary school teachers, the recruitment and selection of candidates. In this case, there is a tendency to prioritize teachers who have a close relationship with the policy makers in the Department of Education and the Regional Employment Board. Third, there are two patterns of supervision undertaken in the development of quality of primary school teachers in Tegal, Central Java, namely and indirect direct supervision. Direct supervision is carried out through regular meetings between the Office of Education with teachers who attend the development programs. Indirect supervision is carried out through analysis of the progress report of participants' improvement. Fourth, the development of quality teachers has increased the percentage of S1-graduated primary school teachers ie., 18.27% in 2003; 21.30% in 2005; and 24% in 2007, and the number of primary school teachers participating in the development of quality of teachers through training programs. In 2003, there were approximately 11.29% elementary school teachers, increased to 15% (2005), and 34.30% (2007). Its positive impact is the improvement: (1) educational background of teachers; (2) the ability to teach; (3) the level mastery of subjects and educational perspectives; (4) teachers' performance, and (5) elementary education efficiency rate. Conceptual model of management of quality performance development of primary school teachers which can be implemented within the framework of improving the quality of elementary education in Tegal, Central Java, is the one that meets the assumption of standards of teachers' competence, the strategic position of primary schools and elementary school teachers, and the autonomy of educational resource management. The elements include the vision, planning, and implementation criteria, which as a whole must support the spirit of improving the efficiency, relevance, effectiveness and accountability of management performance development of quality teachers within the framework of the decentralization policy.